Transnational Volunteers: American Foreign Fighters Combating the Islamic State. Issue 3 (2nd April 2020) - Fritz, Jason; Young, Joseph K.
ABSTRACT: Why do some people go abroad to engage in other people's wars? Some studies attempt to discern why individuals choose to fight in distant lands (Malet, 2013) or seek to count how many do so (Hegghammer, 2013). The term foreign fighter has been used nearly exclusively in recent research to describe transnational fighters who join with Islamist organizations, or more generally for individuals fighting with resistance groups against a state. However, little research has been done on the many transnational fighters who travel to fight against resistance groups or against Islamist organizations. Our paper examines these transnational militants who battle against the Islamic State, focusing on Americans who engage in such activities, often referred to as volunteers. Through a review of open-source media, we created a dataset of these individuals, recording demographic data such as each individual's military experience and stated purpose for becoming a transnational fighter. We show descriptive analyses on these data, and then compare these findings against current scholarship on Islamist transnational fighters. We argue that American volunteers and foreign terrorist fighters are phenomena with difference in degree, but not in kind.